(untitled) (Heritage, 2023)
The new time is a period when organizations and employees are facing radical changes on a daily basis. The Covid pandemic has made the existing situation even more complex, and has posed new challenges to organizations, and their employees. Adapting to the “new normality” requires multispectral changes within the organizational structure, culture, work practices, and lifestyle. It is to be expected that the fear of change is ubiquitous, however, this is one of the situations when the crisis should be seen as a potential chance. The authors made an effort to describe and explain the organizational aspects of change in more detail, all with the aim of promoting current business practices.